Fibrous Dysplasia of the Orbit in a 5-Year-Old Girl - Torabi, Hamidreza; Sadeghi Tari, Ali (Journal of Ophthalmic and Optometric Sciences, 2017)
Purpose: The aim of the present study was to describe a case of orbital fibrous dysplasia in a very young child. Case report: A 5-year-old girl presented with unilateral, painless, slowly progressive proptosis of the left eye and inferotemporal globe displacement from about 1 year ago. The visual acuity in both eyes was 20/20. The general physical examination was normal. Computed tomography (CT scan) revealed thickening and deformity of the orbital walls. Lateral orbitotomy and biopsy were performed and were compatible with fibrous dysplasia. Conclusion: Craniofacial fibrous dysplasia usually occurs in the second decade of life, but it can also rarely present in the early years of life. Therefore, fibrous dysplasia should be considered as a differential diagnosis of proptosis or globe displacement in the early years of life. Keywords: Fibrous; Dysplasia; Orbit; Child; Iran.